Sphingosine 1-Phosphate Signaling as a Target in Hepatic Fibrosis Therapy - Bárbara González-Fernández; Diana I. Sánchez; Javier González-Gallego; Javier González-Gallego; María J. Tuñón; María J. Tuñón (Frontiers Media S.A., 2017)
Liver fibrosis is an excess production of extracellular matrix proteins as a result of chronic liver disease which leads to cell death and organ dysfunction. The key cells involved in fibrogenesis are resident hepatic stellate cells (HSCs) which are termed myofibroblasts after activation, acquiring contractile, proliferative, migratory and secretory capability. Sphingosine 1-phosphate (S1P) is a bioactive sphingolipid with well-established effects on angiogenesis, carcinogenesis and immunity. Accumulating evidence demonstrates that this metabolite is involved in the profibrotic inflammatory process through the regulation of pleiotropic cell responses, such as vascular permeability, leukocyte infiltration, cell survival, migration, proliferation and HSCs differentiation to myofibroblasts. S1P is synthesized by sphingosine kinases (SphKs) and many of its actions are mediated by S1P specific cell surface receptors (S1P1-5), although different intracellular targets of S1P have been identified. Modulation of SphKs/S1P/S1P receptors signaling is known to result in beneficial effects on various in vivo and in vitro models of liver fibrosis. Thus, a better knowledge of the molecular mechanisms involved in the modulation of the S1P pathway could help to improve liver fibrosis therapy. In this review, we analyze the effects of the S1P axis on the fibrogenic process, and the involvement of a range of inhibitors or approaches targeting enzymes related to S1P in the abrogation of pathological fibrogenesis. All in all, targeting this pathway offers therapeutic potential in the treatment of hepatic fibrosis.